2007
DOI: 10.1063/1.2719197
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the millimeter-wave collective Thomson scattering system of the high-field tokamak Frascati Tokamak Upgrade

Abstract: We first describe the improved receiving system of the diagnostic experiment of millimeter-wave collective Thomson scattering being run on the Frascati Tokamak Upgrade (FTU), and then discuss some peculiar problems and new operating procedures related to the investigation of strong anomalous spectra of nonthermal origin, many-orders-of-magnitude stronger than the ion thermal feature merged in them, systematically observed in the experimentation, and finally ascribed to a perturbation of the gyrotron that gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Previous measurements [2][3] were carried out in an updown symmetric scattering geometry accommodated in the narrow vertical ports and providing a scattering angle θ ≅90 o . The experimentation was generally performed with B T ≤7.2T on the vessel axis, with the probing beam that had to cross the EC resonance and the nearby upper-hybrid (UH) cut-off for the X mode at a position inside the beam injection port.…”
Section: Introductionmentioning
confidence: 99%
“…Previous measurements [2][3] were carried out in an updown symmetric scattering geometry accommodated in the narrow vertical ports and providing a scattering angle θ ≅90 o . The experimentation was generally performed with B T ≤7.2T on the vessel axis, with the probing beam that had to cross the EC resonance and the nearby upper-hybrid (UH) cut-off for the X mode at a position inside the beam injection port.…”
Section: Introductionmentioning
confidence: 99%
“…However, one may expect that by refinement of the experimental setup and future development of the analysis one should be able to determine other plasma parameters such as the ion temperature T i with a higher accuracy than in present CTS-based methods (see, e.g., Ref. [24]). …”
Section: Prl 106 165004 (2011) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…The CTS installed on the FTU tokamak which runs at below fundamental have also seen similar phenomenã where they refer it to "anomalous spectra" and concluded that is was caused by backreflections from breakdown plasma or arcs in the transmission line. 18 There are currently three hypothesis: the first is that spurious signals intrinsically come from the gyrotron for specific gyrotron parameter settings ͑beam voltage, coil current, etc.͒ where the conversion efficiency it not optimized and cause parasitic oscillations. The second hypothesis is backreflected radiation from either a surface or from arcs in the transmission line that affects the electron beam in the resonator causing spurious signal.…”
Section: Spurious Signals In the Receivermentioning
confidence: 99%